Peacemaking affordances of shareable interfaces: a provocative essay on using technology for social change - Ioannou, Andri; Antoniou, Chrystalla G. (My University, 2017)
This article is a provocative essay on the topic of educational applications of shareable interfaces, with a focus on the use of multitouch interactive tabletops in peacemaking school initiatives. Based on the already researched affordances of tabletops in education, as well as promising empirical results from the limited application of this technology in peacemaking contexts, the authors of this manuscript would argue for the integration and further investigation of interactive tabletops in peacemaking school initiatives, pushing the boundaries of the technology to positively influence our societies.
Keywords: Multitouch tabletops; Peace and technology; Peace education; Peacebuilding; Peacemaking; Shareable interfaces; Technology enhanced learning